Menakar Kembali Legitimasi Teologis Gender: Reassessing the Theological Legitimacy of Gender - Ali Hasan Siswanto (An-Nisa’ Journal of Gender Studies, 2010)
Islam was born in the midst of a society of ignorance, a time when a mother who gave birth to a baby girl would be buried alive, or if left alive, she would be subjected to ridicule, insults, and abuse. Islam came to eradicate intimidation and discrimination against women. Islam came with the principle that Allah created humans to serve Him without distinguishing between genders. At this level, Islam sides with women, but some conventional scholars' thoughts on women are still identified as considering “behavior” and “attitude of women” to be translated into “women's nature” which cannot be changed from its origin, namely “serving” men. Based on this background, the author uses critical reasoning to re-examine the theological aspects that legitimize male superiority. As a result, it is necessary to reconstruct the understanding of texts that contain gender bias. Islam lahir di tengah masyarakat jahiliyah, suatu masa ketika seorang ibu melahirkan bayi wanita akan dikuburkan hiduphidup, atau jika dibiarkan hidup ia akan menanggung cercaan, hinaan dan celaan. Islam datang untuk memberangus intimidasi dan diskriminasi perempuan. Islam datang dengan prinsip bahwa Allah menciptakan manusia untuk mengabdi kepada-Nya dengan tidak membeda-bedakan jenis kelamin. Pada taraf ini Islam berpihak kepada wanita, namun beberapa pemikiran ulama konvensional tentang wanita teridentifikasi masih menganggap "tingkah laku" dan "sikap wanita" diterjemahkan menjadi “kodrat wanita" yang tidak dapat diubah dari asalnya yaitu "mengabdi" kepada laki-laki. Berangkat dari latar belakang ini, penulis menggugah dengan nalar kritis untuk kembali menelusuri sisi teologis yang menjadi legitimasi terhadap superioritas laki-laki. Alhasil, perlu rekonstruksi terhadap pemahaman teks yang mengandung bias gender.